Gamma Probe Radioguided Parathyroid Forearm Surgery in Recurrent Hyperparathyroidism - Cutress, RI (The Royal College of Surgeons of England, 2009)
A case is described of a successful radioguided forearm graft parathyroidectomy. This is the first report of both pre-operative diagnostic and successful intra-operative localisation during a single procedure, of autologous transplanted parathyroid tissue.